Isolating membrane, preparation method thereof, and related secondary battery and electric device
Patent Information
- Application Number
- CN202280096454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-01-03
AI Technical Summary
Existing secondary battery separators have poor heat resistance after thinning design and are prone to thermal shrinkage, causing short circuits between the positive and negative electrodes, increasing safety risks, and having poor mechanical properties, affecting safety performance.
Silicone particles are used as the coating material, and by regulating its volume distribution particle size Dv90 and particle size distribution, a thin and uniform coating is formed, which improves the heat resistance and stability of the isolation film and ensures the isolation effect of the positive and negative electrodes.
It achieves a lightweight and thin design of the isolation film, improves the safety performance and mechanical performance of the secondary battery, reduces the risk of thermal shrinkage, and improves the electrochemical performance and cycle life.
Smart Images

Figure CN119256442A_ABST
Abstract
Description
Separator, preparation method thereof, and related secondary battery and electric device Technical Field
[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices. Background Art
[0002] Secondary batteries have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, and power tools, etc.
[0003] As battery applications become increasingly widespread, the requirements for secondary battery performance are becoming increasingly stringent, especially the safety performance of secondary batteries. How to further improve the safety performance of batteries during use remains one of the topics that technicians in this field need to continuously break through.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator, a preparation method thereof, and related secondary batteries and electrical devices.
[0006] A first aspect of the present application provides an isolation membrane, which includes a substrate and a coating provided on at least one surface of the substrate, wherein the coating includes silicone particles, and the volume distribution particle size Dv90 of the silicone particles satisfies: 0<Dv90≤3.0μm.
[0007] In some embodiments, 0.1 μm ≤ Dv90 ≤ 2.0 μm.
[0008] Therefore, the present application sets 0<Dv90≤3.0μm, especially when 0.1μm≤Dv90≤2.0μm, the particle size of the silicone particles is less than or equal to the thickness of the coating, which is conducive to the formation of a coating with a smaller thickness, thereby obtaining an isolation film with a thinner overall thickness; and because the coating has good heat resistance and stability, the isolation film can effectively isolate the positive and negative electrodes of the secondary battery, thereby improving the safety performance of the secondary battery.
[0009] In some embodiments, the particle size distribution of the organosilicon particles satisfies: (Dv90-Dv10) / Dv50≤2.0; alternatively, 0.1≤(Dv90-Dv10) / Dv50≤1.0.
[0010] Therefore, when the particle size distribution of the silicone particles in the present application meets the above range, the particle size distribution of the silicone particles is relatively uniform, which is conducive to the uniform dispersion of the silicone particles in the coating and the formation of a coating with relatively uniform thickness.
[0011] In some embodiments, the volume distribution particle size Dv50 of the organosilicon particles satisfies: 0.01 μm≤Dv50≤2 μm.
[0012] Therefore, the volume distribution particle size Dv50 of the silicone particles in this application is set to meet the following requirements: 0.01μm≤Dv50≤2μm, which can meet the requirement of coating a smaller thickness of the isolation membrane. At the same time, the above-mentioned particle size enables a tight overlap between the silicone particles in the coating. When the isolation membrane is heated, the silicone particles quickly contact and squeeze to apply force, giving tension to the substrate and reducing the risk of substrate shrinkage, thereby ensuring that the isolation membrane effectively isolates the positive and negative electrodes and improving the safety performance of the secondary battery.
[0013] In some embodiments, the specific surface area (SSA) of the silicone particles is 2.0 cm 2 / g to 50cm 2 / g, optional 8.5cm 2 / g to 20.5cm 2 / g.
[0014] Therefore, when the specific surface area SSA of the silicone particles is within the above range, the specific surface area SSA of the silicone particles is relatively large, which is conducive to good overlap between the particles, making it easier to form a pore structure between the silicone particles, which is conducive to the migration of active ions.
[0015] In some embodiments, the organosilicon particles include primary particles. The primary particles have a relatively small particle size, which facilitates uniform dispersion of the organosilicon particles when applied to a coating, resulting in a more uniform film performance.
[0016] In some embodiments, the morphology of the organosilicon particles includes at least one of spherical, quasi-spherical, cubic, rhombic, fibrous, tubular, rod-like, and flake-like. The organosilicon particles may be randomly arranged, which facilitates better overlap and increases contact points between particles, thereby improving the overall shrinkage resistance of the coating and providing a more stable structure for the separator.
[0017] In some embodiments, the organosilicon particles include a first polymer, the first polymer including a first structural unit, a second structural unit, and a third structural unit; the first structural unit includes a structural unit represented by formula (I):
[0018]
[0019] In formula (I),
[0020] R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; R2 includes one or more of a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C1-C20 hydroxyalkyl group; alternatively, R2 includes one or more of a C1-C12 alkyl group, a C3-C12 cycloalkyl group, or a C1-C12 hydroxyalkyl group;
[0021] The second structural unit includes a structural unit represented by formula (II):
[0022]
[0023] In formula (II), R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group;
[0024] The third structural unit includes a structural unit represented by formula (III):
[0025]
[0026] In formula (III), R4 to R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, one or more structural units as shown in formula (III-1), and R4 to R 11 At least one of them is a structural unit represented by formula (III-1),
[0027]
[0028] In formula (III-1), R 12 Including one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R 12 Including one or more of hydrogen atom, substituted or unsubstituted C1-C3 alkyl; R 13 Including substituted or unsubstituted C1-C10 alkyl; optionally, R 13 This includes substituted or unsubstituted C3-C10 alkyl groups.
[0029] In some embodiments, the organosilicon particles include a second polymer comprising a structural unit represented by formula (a):
[0030]
[0031] In formula (a), R 14 and R 15Each independently comprises one or more of substituted or unsubstituted C1-C10 alkyl, hydroxyl or amino; optionally, R 14 and R 15 Each independently includes one or more of a substituted or unsubstituted C1-C6 alkyl group, a hydroxyl group or an amino group.
[0032] Optionally, the second polymer includes one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane and polymethylaminosiloxane.
[0033] Therefore, when the organic silicon particles include a polymer of the above structural units, the heat resistance and stability of the entire separator can be further improved.
[0034] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is recorded as A%, 75≤A<100; optionally, 75≤A≤80.
[0035] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is recorded as B%, 0<B≤15; optionally, 5≤B≤15.
[0036] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is recorded as C%, 0<C≤15; optionally, 5≤C≤15.
[0037] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is recorded as A%, the molar content of the second structural unit is recorded as B%, and the molar content of the third structural unit is recorded as C%; the first polymer satisfies one or more of conditions (1) to (3): (1) 5≤A / B≤15; (2) 5≤A / C≤15; (3) A:B:C is (12 to 15): (1 to 3): (1 to 3).
[0038] In some embodiments, the number average molecular weight of the organosilicon particles is 22,000 to 79,000, and optionally 24,000 to 48,000. When the number average molecular weight of the organosilicon particles is within the above range, they have a relatively high viscosity, which is beneficial for improving the adhesion between the separator and the positive and negative electrode sheets when the organosilicon particles are used in the separator.
[0039] In some embodiments, the moisture content of the organosilicon particles is less than or equal to 3500 μg / g, and can optionally be between 500 μg / g and 3000 μg / g, based on the mass of the organosilicon particles. When the moisture content of the organosilicon particles is within this range, the relatively low moisture content can reduce the risk of side reactions in the electrolyte during long-term charge and discharge cycles of the secondary battery, thereby improving the electrochemical performance of the secondary battery.
[0040] In some embodiments, based on the mass of the coating, the mass percentage of the organosilicon particles is m1%, 50≤m1<100, optionally, 80≤m1≤95; thereby, the heat resistance and stability of the coating can be ensured.
[0041] In some embodiments, the coating further comprises inorganic particles; optionally, the mass percentage of the inorganic particles in the coating is m2%, 0<m2≤30. By adding inorganic particles, the heat resistance of the coating can be further improved.
[0042] In some embodiments, the isolation film further satisfies at least one of conditions (a) to (c): (a) the porosity of the substrate is greater than or equal to 25%, optionally ranging from 28% to 41%; (b) the thickness of the substrate is less than or equal to 16 μm, optionally ranging from 3 μm to 12 μm; and (c) the thickness of the coating is 0.1 μm to 4 μm, optionally ranging from 0.5 μm to 3 μm. When the isolation film meets the above conditions, the heat resistance and lightweight design of the isolation film can be further improved.
[0043] In some embodiments, the isolation film further comprises at least one of the following conditions (I) to (VII): (I) the longitudinal heat shrinkage rate η1 of the isolation film at 150°C and 1 hour is ≤3.0%; (II) the transverse heat shrinkage rate η2 of the isolation film at 150°C and 1 hour is ≤2.0%; (III) the longitudinal tensile strength R of the isolation film is less than or equal to 0. m1 ≥2700kgf / cm 2 , optionally, 2700kg / cm 2 ≤R m1 ≤4500kg / cm 2 (IV) the transverse tensile strength R of the isolation film m2 Degree ≥2000kgf / cm 2 , optionally, 2500kg / cm 2 ≤R m2 ≤4500kg / cm 2; (V) the wetting length L of the isolation membrane is ≥30 mm, optionally, 30 mm ≤ L ≤ 60 mm; (VI) the wetting speed u of the isolation membrane is ≥2 mm / s, optionally, 2 mm / s ≤ u ≤ 4 mm / s; (VII) the air permeability MAP of the isolation membrane is ≤300 s / 100 mL, optionally, 130 secs / 100 mL ≤ MAP ≤ 250 secs / 100 mL.
[0044] The second aspect of the present application provides a method for preparing an isolation membrane, which is used to prepare the isolation membrane of any embodiment of the first aspect of the present application, and the method includes: S1, providing a substrate; S2, mixing silicone particles in a solvent to prepare a coating slurry; S3, applying the coating slurry on at least one surface of the substrate to form a coating and drying to obtain an isolation membrane, wherein the volume distribution particle size Dv90 of the silicone particles satisfies: 0<Dv90≤3.0μm; optionally, 0.1μm≤Dv90≤2.0μm.
[0045] In some embodiments, based on the mass of the coating, the mass percentage of the silicone particles is greater than or equal to 50%; optionally 80% to 95%; and / or the solid content of the coating slurry is 10% to 40%; optionally 20% to 30%.
[0046] A third aspect of the present application provides a secondary battery, comprising an isolation membrane according to any embodiment of the first aspect of the present application or an isolation membrane prepared by the preparation method according to any embodiment of the second aspect of the present application.
[0047] A fourth aspect of the present application provides an electrical device comprising the secondary battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0049] FIG1 is a schematic diagram of an embodiment of a secondary battery of the present application.
[0050] FIG. 2 is an exploded schematic diagram of an embodiment of the secondary battery of FIG. 1 .
[0051] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.
[0052] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.
[0053] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0054] FIG6 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source.
[0055] The drawings are not necessarily drawn to scale.
[0056] The following are the descriptions of the reference numerals:
[0057] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0058] 5. Secondary battery; 51. Housing; 52. Electrode assembly;
[0059] 53. Cover plate;
[0060] 6. Electrical equipment. DETAILED DESCRIPTION
[0061] The following detailed description specifically discloses the embodiments of the separator, its preparation method, and related secondary batteries and electrical devices of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0064] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0065] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0066] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0067] In this application, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance.
[0068] In this application, the terms "plurality" and "multiple" refer to two or more.
[0069] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0070] Unless otherwise stated, the numerical values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application.
[0071] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1 to C50 alkyl group, a C1 to C40 alkyl group, a C1 to C30 alkyl group, a C1 to C20 alkyl group, a C1 to C12 alkyl group, a C1 to C10 alkyl group, a C1 to C6 alkyl group, or a C1 to C4 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, or the like. In addition, the alkyl group may be optionally substituted.
[0072] When the above groups are substituted, the substituent group may be a halogen atom or a heteroatom. Alternatively, the heteroatom may include a nitrogen atom; the substituent group may be a nitrogen atom or a halogen atom.
[0073] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0074] The term "heteroatom" refers to a nitrogen atom, a sulfur atom, a phosphate atom, and the like.
[0075] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0076] In various places of this specification, the substituents of compounds are disclosed in groups or ranges. It is clearly expected that this description includes each individual subcombination of the members of these groups and ranges. For example, it is clearly expected that the term "C1 to C8 alkyl" discloses C1, C2, C3, C4, C5, C6, C7, C8, C1 to C8, C1 to C7, C1 to C6, C1 to C5, C1 to C4, C1 to C3, C1 to C2, C2 to C8, C2 to C7, C2 to C6, C2 to C5, C2 to C4, C2 to C3, C3 to C8, C3 to C7, C3 to C6, C3 to C5, C3 to C4, C4 to C8, C4 to C7, C4 to C6, C4 to C5, C5 to C8, C5 to C7, C5 to C6, C6 to C8, C6 to C7 and C7 to C8 alkyl.
[0077] As further examples, the integers in the range of 5 to 40 are specifically contemplated as individually disclosing 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40; the integers in the range of 1 to 20 are specifically contemplated as individually disclosing 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Additional groups or ranges are expressly contemplated accordingly.
[0078] Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. Its main function is to prevent the positive electrode sheet and the negative electrode sheet from short-circuiting, while allowing active ions to pass freely to form a loop.
[0079] With the application and promotion of secondary batteries, people have higher and higher requirements for secondary battery energy density. Thinning the separator is an effective measure to improve the energy density of secondary batteries.
[0080] While designing separator thinning, the inventors discovered that separators, typically made of porous polyolefin membranes such as polyethylene porous membranes, polypropylene porous membranes, or polypropylene / polyethylene / polypropylene three-layer composite membranes, exhibit poor heat resistance after thinning. When heated, they experience significant thermal shrinkage, which can lead to direct contact between the positive and negative electrodes within the battery, resulting in internal short circuits and increased safety risks for the secondary battery. Furthermore, thinning the separators also results in poor mechanical properties and increased deformation, further impacting the safety of the secondary battery.
[0081] In view of this, the inventors proposed an isolation membrane, which includes a substrate and a coating. By further regulating the volume distribution particle size Dv90 of the coating, the coating thickness can be made smaller, which is conducive to the overall lightweight design of the isolation membrane. The technical solution of this application is described in detail below.
[0082] Isolation film
[0083] In a first aspect, the present application provides an isolation membrane.
[0084] The isolation film includes a substrate and a coating disposed on at least one surface of the substrate, the coating includes organic silicon particles, and the volume distribution particle size Dv90 of the organic silicon particles satisfies: 0<Dv90≤3μm; optionally, 0.1μm≤Dv90≤2μm.
[0085] The coating applied to the substrate includes organosilicon particles. Organosilicon refers to an organosiloxane with a main chain consisting of a silicon-oxygen-silicon bond (-Si-O-Si-). Since the silicon-oxygen-silicon bond is an inorganic bond with a high bond energy, it can impart high heat resistance and chemical stability to the organosilicon. For example, the organosilicon can be used for long periods of time below 200°C. The side chains of the organosilicon can be grafted with organic groups or not. Grafting organic groups can impart good dispersibility to the organosilicon, thereby improving the coating performance of the organosilicon coating and its affinity with the substrate. The dispersion of the organosilicon particles in the coating imparts good heat resistance to the coating, and the formation of a structure with voids between the organosilicon particles increases the ion conduction channels of the separator, promoting the transport of active ions. At the same time, it can enhance the separator's wettability and retention of the electrolyte. When used in a secondary battery, the separator can improve the battery's long cycle life and good rate performance.
[0086] The inventors discovered that when designing a thinner isolation membrane, the substrate, as the main supporting structure of the isolation membrane, needs to meet certain mechanical properties. Since mechanical properties and thickness have a certain positive correlation, the thickness of the substrate must be guaranteed, which prevents the thickness of the substrate from being reduced indefinitely. While the coating, as a functional layer structure on the substrate, can be thinned, the particle size of the silicone particles in the coating limits the coating thickness. In particular, the volume distribution particle size Dv90 of the silicone particles affects the minimum coating thickness. A larger volume distribution particle size Dv90 corresponds to a thicker coating, which is detrimental to overall thinning of the isolation membrane. A smaller volume distribution particle size Dv90 facilitates the formation of a thinner coating, which facilitates overall thinning of the isolation membrane. This application sets the limit of 0 < Dv90 ≤ 3.0 μm. The particle size of the silicone particles is less than or equal to the thickness of the coating, which facilitates the formation of a thinner coating, thereby achieving a thinner separator. Furthermore, due to the coating's excellent heat resistance and stability, the separator can effectively isolate the positive and negative electrodes of the secondary battery, thereby improving the safety of the secondary battery. Alternatively, 0.1 μm ≤ Dv90 ≤ 2.0 μm. For example, the volume distribution particle size Dv90 of the silicone particles can be 0.05, 0.1, 0.2, 0.5, 0.8, 1.0, 2.0, 2.2, 2.5, 2.8, 3.0, or a range consisting of any two of the foregoing values.
[0087] In some embodiments, the particle size distribution of the organosilicon particles satisfies: (Dv90-Dv10) / Dv50≤2.0.
[0088] When the particle size distribution of the silicone particles meets the above range, the particle size distribution of the silicone particles is relatively uniform, which is conducive to the uniform dispersion of the silicone particles in the coating, forming a coating with a relatively uniform thickness. In addition, when the coating slurry is applied to the surface of the substrate, the risk of the silicone particles falling into the gaps in the substrate can be reduced, thereby ensuring the air permeability of the substrate; because the silicone particles are mainly distributed in the coating, the heat resistance of the coating as a whole can be guaranteed. Optionally, 0.1≤(Dv90-Dv10) / Dv50≤1.0; illustratively, (Dv90-Dv10) / Dv50 can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.5, 0.6, 0.8, 0.9, 1.0, 1.2, 1.5, 1.8, 2.0 or a range consisting of any two of the above values.
[0089] In some embodiments, the volume distribution particle size Dv50 of the organosilicon particles satisfies: 0.01 μm≤Dv50≤2 μm.
[0090] When the volume distribution particle size Dv50 of the silicone particles is too small, the particle size of the silicone particles is relatively small. When the coating slurry that forms the coating is applied on the surface of the substrate, the silicone particles are easily deposited in the gaps of the substrate as the slurry flows, resulting in a decrease in the overall air permeability of the isolation membrane and poor ion conductivity. During the charge and discharge process of the secondary battery, the isolation membrane has a poor effect in conducting ions, which in turn reduces the dynamic performance of the secondary battery.
[0091] When the volume distribution particle size Dv50 of the silicone particles is too large, 3 to 5 layers of silicone particles are piled up between each other, which can easily lead to an overly thick coating, making the overall thickness of the isolation membrane thicker; and, when the silicone particles are too large, it is difficult for the silicone particles to form an effective overlap when the coating is applied. The larger gaps between the particles make it easy for the silicone particles to slowly come into contact with the isolation membrane as the substrate shrinks when heated, resulting in deterioration of the heat resistance of the isolation membrane. The shrinkage of the isolation membrane can easily lead to a deterioration in the isolation effect on the positive and negative electrodes, making it easy for a short circuit to occur between the positive and negative electrodes.
[0092] Therefore, the present application sets the volume distribution particle size Dv50 of the silicone particles to meet the following requirements: 0.01μm≤Dv50≤2μm, which can meet the requirement of applying a smaller thickness to the isolation film coating. At the same time, the above particle size allows the silicone particles in the coating to form a tight overlap. When the isolation film is heated, the silicone particles quickly contact and squeeze each other, applying tension to the substrate, reducing the risk of substrate shrinkage, thereby ensuring that the isolation film effectively isolates the positive and negative electrode sheets, and improving the safety performance of the secondary battery. For example, the volume distribution particle size Dv50 of the silicone particles can be 0.01μm, 0.05μm, 0.08μm, 0.1μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, or a range consisting of any two of the above values.
[0093] In some embodiments, the volume distribution particle size Dv10 of the organosilicon particles satisfies: 0.01 μm≤Dv10≤2.80 μm.
[0094] When the volume distribution particle size Dv10 of the silicone particles satisfies the above range, the particle size distribution of the silicone particles is relatively concentrated, thereby facilitating uniform coating thickness. For example, the volume distribution particle size Dv10 of the silicone particles can be 0.01 μm, 0.02 μm, 0.05 μm, 0.08 μm, 0.10 μm, 0.15 μm, 0.20 μm, 0.50 μm, 0.80 μm, 1.00 μm, 1.20 μm, 1.50 μm, 1.80 μm, 2.00 μm, 2.20 μm, 2.50 μm, 2.80 μm, or a range consisting of any two of the above values.
[0095] In this application, the volume distribution particle size Dv90 of a material is generally known in the art and represents the particle size corresponding to 90% of the cumulative volume distribution percentage of the material. This can be measured using instruments and methods known in the art. For example, the particle size distribution can be measured using a laser particle size analyzer (e.g., Master Size 3000) in accordance with GB / T 19077-2016, Laser Diffraction Method.
[0096] In this application, the volume distribution particle size Dv50 of a material is generally known in the art and represents the particle size corresponding to 50% of the cumulative volume distribution percentage of the material. This can be measured using instruments and methods known in the art. For example, the particle size distribution can be measured using a laser particle size analyzer (e.g., Master Size 3000) in accordance with GB / T 19077-2016, Laser Diffraction Method.
[0097] In this application, the volume distribution particle size Dv10 of a material has a well-known meaning in the art, representing the particle size corresponding to 10% of the cumulative volume distribution percentage of the material. It can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer (e.g., Master Size 3000) in accordance with GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.
[0098] In some embodiments, the specific surface area (SSA) of the silicone particles is 2.0 cm 2 / g to 50cm 2 / g, optional 8.5cm 2 / g to 20.5cm 2 / g.
[0099] When the specific surface area SSA of the silicone particles is within the above range, the specific surface area SSA of the silicone particles is relatively large, which is conducive to good overlap between the particles, making it easier to form a pore structure between the silicone particles, which is conducive to the migration of active ions. For example, the specific surface area SSA of the silicone particles can be 2.0 cm 2 / g, 5.0cm 2 / g, 8.0cm 2 / g, 8.5cm 2 / g, 10.0cm 2 / g, 15.0cm 2 / g, 20.0cm 2 / g, 20.5cm 2 / g, 25.0cm 2 / g, 30.0cm 2 / g, 35.0cm 2 / g, 40.0cm 2 / g, 42.0cm 2 / g, 45.0cm 2 / g, 48.0cm 2 / g, 50.0cm 2 / g or a range consisting of any two of the above values.
[0100] The specific surface area (SSA) of the organosilicon particles can be measured using methods known in the art. For example, the specific surface area (SSA) can be measured using the nitrogen adsorption specific surface area analysis method described in GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Micromeritics Tri-Star 3020 specific surface area pore size analyzer.
[0101] The inventors further discovered that the morphology of the silicone particles has a certain influence on the coating. When the morphology of the silicone particles meets the following conditions, the heat resistance and stability of the isolation membrane can be further improved.
[0102] In some embodiments, the morphology of the organosilicon particles includes at least one of sphere, spheroid, cube, rhombus, fiber, tube, rod, and plate.
[0103] When the organosilicon particles are spherical and / or quasi-spherical, they can ensure good overlap between the particles, improve the heat resistance and stability of the coating, and the presence of gaps between the particles is conducive to building a stable spatial network structure, thereby improving the ion transmission characteristics and resistance to external force extrusion of the separator. In addition, the gaps between the spherical and / or quasi-spherical particles are large, which can reduce the effect of the coating on the air permeability of the substrate, further improve the overall air permeability and ion conductivity of the separator, and enhance the dynamic performance of the secondary battery. Furthermore, the larger porosity between the spherical and / or quasi-spherical particles is conducive to improving the wettability of the separator to the electrolyte and the liquid retention rate and liquid retention rate of the separator, further improving the dynamic performance of the secondary battery; and the larger porosity can have a weight-reducing effect, which is conducive to improving the energy density per unit weight of the secondary battery; and it can reduce the amount of organosilicon particles in the coating, which is conducive to reducing the cost of the secondary battery.
[0104] When the silicone particles are in the shape of cubes, diamonds, fibers, tubes, rods or sheets, the silicone particles can be arranged irregularly, which is conducive to better overlap between the particles and increases the contact points between the particles, thereby helping to improve the overall shrinkage resistance of the coating and making the overall structure of the isolation film more stable.
[0105] Especially when the organosilicon particles include two or more morphologies, the overlap between the particles is tighter, thereby further improving the overall shrinkage resistance of the coating and making the overall structure of the isolation film more stable.
[0106] For example, the organosilicon particles include spherical, cubic, and other morphologies. Alternatively, the organosilicon particles include cubic, diamond, and other morphologies.
[0107] In some embodiments, the organosilicon particles include primary particles. The primary particles have a relatively small particle size, which facilitates uniform dispersion of the organosilicon particles when applied to a coating, resulting in a more uniform film performance.
[0108] In the present application, the morphology of the organosilicon particles can be observed by a scanning electron microscope (SEM), for example, a JSM-5610LV scanning electron microscope manufactured by FEI Company of the United States is used to observe the morphology after vacuum gold spraying on the sample.
[0109] As a polymer, silicone can further improve the heat resistance and stability of the entire separator when the polymer meets at least one of the following conditions.
[0110] In some embodiments, the organosilicon particles include a first polymer including a first structural unit, a second structural unit, and a third structural unit.
[0111] The first structural unit includes a structural unit represented by formula (I):
[0112]
[0113] In formula (I), R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; R2 includes one or more of a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C1-C20 hydroxyalkyl group; alternatively, R2 includes one or more of a C1-C12 alkyl group, a C3-C12 cycloalkyl group, or a C1-C12 hydroxyalkyl group.
[0114] The second structural unit includes a structural unit represented by formula (II):
[0115]
[0116] In formula (II), R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.
[0117] The third structural unit includes a structural unit represented by formula (III):
[0118]
[0119] In formula (III), R4 to R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, one or more structural units as shown in formula (III-1), and R4 to R 11 At least one of them includes a structural unit represented by formula (III-1),
[0120]
[0121] In formula (III-1), R 12 Including one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R 12 Including one or more of hydrogen atom, substituted or unsubstituted C1-C3 alkyl; R13 Including substituted or unsubstituted C1-C10 alkyl; optionally, R 13 This includes substituted or unsubstituted C3-C10 alkyl groups.
[0122] The first structural unit can be formed by opening the carbon-carbon double bond of an acrylate monomer during the polymerization process. The flexible monomer segments within the molecular chain can adjust the glass transition temperature of the first polymer, improving its toughness and peel strength, thereby contributing to a good adhesive bond with the substrate and reducing the risk of the coating peeling from the substrate. The second structural unit can be formed by opening the carbon-carbon double bond of an acrylonitrile monomer during the polymerization process. This second structural unit can produce excellent swelling resistance and high adhesion, and can help improve the ionic conductivity of the secondary battery.
[0123] The third structural unit is formed by opening the carbon-carbon double bond of the substituted or unsubstituted acryloxy group of polysilsesquioxane during the polymerization process. Polysilsesquioxane can be considered as a material containing an organic-inorganic hybrid core-shell structure, wherein the internal inorganic framework serves as the core, i.e., a skeleton structure composed of Si-O-Si or Si-O bonds; the outer shell is composed of organic substituents (C1-C5 alkyl groups), which are wrapped around the skeleton structure and connected to the Si element of the skeleton structure. The core structure of polysilsesquioxane can give the polymer advantages in heat resistance and mechanical properties. Its poor shrinkage can ensure the stability of the polymer during the long-term cycle charge and discharge process of the secondary battery, effectively isolating the positive and negative electrodes, thereby ensuring the safety performance of the secondary battery. In addition, due to the small particle size and large specific surface area of polysilsesquioxane, it is similar to most polymer chain segments in physical scale, which makes the atoms on the surface of polysilsesquioxane have high reactivity. The polymer modified with polysilsesquioxane has good heat resistance, flame retardancy and antioxidant properties.
[0124] Although the above analysis is based on individual structural units, the synergistic effect between the structural units cannot be ignored. Specifically, the first structural unit, the second structural unit, and the third structural unit can work together to improve the bonding and heat resistance of the first polymer in the silicone particles, thereby ensuring the heat resistance of the coating even when the coating is applied thinly.
[0125] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the first structural unit is recorded as A%, and 75≤A<100. When the molar content of the first structural unit is within the above range, its proportion in the first polymer is relatively large, which can improve the flexibility of the first polymer, thereby significantly improving the adhesion of the first polymer; when the first polymer is applied to the isolation membrane, it can improve the bonding force between the silicone particles and the substrate of the isolation membrane. Optionally, 75≤A≤80. For example, the molar content of the first structural unit can be 75%, 78%, 80%, 85%, or a range consisting of any two of the above values.
[0126] In some embodiments, the molar content of the second structural unit, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, is denoted as B%, where 0 < B ≤ 15. When the molar content of the second structural unit is within the above range, the stability of the first polymer can be significantly improved. Alternatively, 5 ≤ B ≤ 15. For example, the molar content of the second structural unit can be 2%, 5%, 8%, 10%, 12%, 15%, or a range consisting of any two of the above values.
[0127] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is recorded as C%, 0<C≤15. When the molar content of the third structural unit is within the above range, the heat resistance of the first polymer can be guaranteed, and its proportion is relatively small, which is beneficial to increase the proportion of the first structural unit and the second structural unit, and improve the overall adhesion, stability and other properties of the first polymer. Optionally, 5≤C≤20. For example, the molar content of the third structural unit can be 2%, 5%, 8%, 10%, 12%, 15% or a range consisting of any two of the above values.
[0128] The first polymer also includes a second structural unit, which can synergize with the first structural unit to improve the anti-swelling and adhesive properties of the first polymer. In particular, when the ratio 5≤A / B≤15 is satisfied, the first structural unit and the second structural unit can further enhance the synergistic effect, improving the adhesiveness and stability of the first polymer. For example, A / B can be 5, 8, 10, 12, 15, or a range consisting of any two of these values.
[0129] The first polymer also includes a third structural unit. The inorganic polysilsesquioxane structure in the third structural unit can synergize with the first structural unit to improve the overall heat resistance and adhesion properties of the first polymer. In particular, when the present application further satisfies the ratio 5≤A / C≤15, the first structural unit and the third structural unit can further effectively synergize with each other to improve the adhesion and heat resistance of the first polymer. For example, A / C can be 5, 8, 10, 12, 15, or a range consisting of any two of these values.
[0130] In some embodiments, A:B:C is (12 to 15):(1 to 3):(1 to 3). When the molar contents of the first structural unit, the second structural unit, and the third structural unit meet the above ratios, the three structural units in the first polymer synergize with each other to improve the adhesion, stability, anti-swelling and thermal stability of the first polymer.
[0131] The first structural unit includes a variety of chemical structures, and the specific chemical structure of the first structural unit is described below.
[0132] In some embodiments, R1 includes a hydrogen atom or a methyl group.
[0133] In some embodiments, R2 comprises methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl, 2-ethylhexyl, dodecyl, or isobornyl.
[0134] Illustratively, the first structural unit includes one or more of the structures represented by formula (I-1) to formula (I-8):
[0135]
[0136] The second structural unit includes a variety of chemical structures, and the specific chemical structure of the second structural unit is described below.
[0137] In some embodiments, R3 includes a hydrogen atom or a methyl group.
[0138] Illustratively, the second structural unit includes one or more of the structures represented by formula (II-1) to the structures represented by formula (II-4):
[0139]
[0140] The third structural unit includes a variety of chemical structures, and the specific chemical structure of the third structural unit is described below.
[0141] In some embodiments, R4 to R 11 Each independently comprises a structural unit as shown in formula (III-1); that is, R4 to R 11All of them include the structural unit shown in formula (III-1), but R4 to R 11 can be the same or different. 12 including hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl or n-pentyl; and / or R 13 These include n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl or 2-ethylhexyl.
[0142] In some embodiments, R4 to R 11 One of them includes a structural unit as shown in formula (III-1); that is, R4 to R 11 There is only one structural unit represented by formula (III-1). 12 including hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl or n-pentyl; and / or R 13 These include n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl or 2-ethylhexyl.
[0143] In the present application, the group types in the polymer can be measured using infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks it contains, thereby determining the type of the modified group. Specifically, the material can be subjected to infrared spectroscopy analysis using instruments and methods well known in the art, for example, using an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet, USA), and tested according to GB / T 6040-2019 General Rules for Infrared Spectroscopy Analysis Methods.
[0144] In some embodiments, the first polymer has an infrared spectrum at 1750 cm -1 to 1735cm -1 , which indicates the presence of ester groups.
[0145] In some embodiments, the first polymer has an infrared spectrum at 2260 cm -1 to 2220cm -1 , which indicates the presence of a cyano group.
[0146] In some embodiments, the first polymer has an infrared spectrum of 1100 nm. -1 to 1120cm -1 The characteristic peaks of silsesquioxane are shown in FIG1 , which indicates the presence of the Si-O-Si skeleton of silsesquioxane.
[0147] In some embodiments, the first polymer can be prepared by the following method, comprising:
[0148] Step S100, providing a first monomer, a second monomer and a third monomer;
[0149] In step S200 , a first monomer, a second monomer, and a third monomer are mixed and polymerized under the action of an initiator to generate a first polymer.
[0150] In the present application, the first monomer, the second monomer and the third monomer are mixed and copolymerized, and the formed first polymer is a copolymer of the three monomers.
[0151] The first monomer includes a structural unit represented by formula (IV),
[0152]
[0153] In formula (IV), in formula (I), R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; R2 includes one or more of a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C1-C20 hydroxyalkyl group; alternatively, R2 includes one or more of a C1-C12 alkyl group, a C3-C12 cycloalkyl group, or a C1-C12 hydroxyalkyl group.
[0154] The first monomer is an acrylic acid ester compound, and when it is polymerized, the carbon-carbon double bond opens to form a first structural unit.
[0155] Illustratively, the first monomer includes one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
[0156] The second monomer includes a structural unit represented by formula (V),
[0157]
[0158] In formula (V), R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.
[0159] The second monomer is an acrylonitrile compound, and when it is polymerized, the carbon-carbon double bond opens to form a second structural unit.
[0160] Illustratively, the second monomer includes acrylonitrile and / or methacrylonitrile.
[0161] The third monomer includes a structural unit represented by formula (VI),
[0162]
[0163] In formula (VI), R 30 to R 37 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, or one or more structural units as shown in formula (VI-1), and R 30 to R 37 At least one of them includes a structural unit represented by formula (VI-1),
[0164]
[0165] In formula (VI-1), R 12 Including one or more of hydrogen atoms, or substituted or unsubstituted C1-C5 alkyl groups; Optionally, R 12 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group;
[0166] R 13 Including substituted or unsubstituted C1-C10 alkyl; optionally, R 13 This includes substituted or unsubstituted C3-C10 alkyl groups.
[0167] Illustratively, the third monomer includes one or more of methacryloxypropyl cage polysilsesquioxane, methacryloxypropyl heptaisobutyl polysilsesquioxane, methacryloxypropyl heptaoctyl polysilsesquioxane, acryloxypropyl cage polysilsesquioxane, acryloxypropyl heptaisobutyl polysilsesquioxane, and methacryloxypropyl heptaoctyl polysilsesquioxane.
[0168] In some embodiments, step S200 specifically includes:
[0169] Step S210, adding a first monomer, a second monomer, and a third monomer into a solvent and an emulsifier and mixing them to form a mixed system;
[0170] In step S220 , an initiator is added to the mixed system, and a polymerization reaction occurs under the action of the initiator to generate a first polymer.
[0171] The present application can copolymerize multiple monomers by emulsion polymerization, which is a simpler polymerization method. Of course, the present application can also adopt other polymerization methods, such as solution polymerization, suspension polymerization, etc. The process parameters used in the polymerization process can be selected from commonly used parameters in the field and will not be repeated here.
[0172] In some embodiments, the emulsifier includes one or more of sodium lauryl sulfate, sodium dodecylbenzene sulfonate, alkyl diphenyl oxide disulfonate, and ammonium ethoxylated alkylphenol sulfate.
[0173] In some embodiments, the ratio of the mass percentage of the emulsifier to the mass percentage of the first, second, and third monomers, based on the total mass of the mixed system, is 0.1% to 5%, i.e., the amount of the emulsifier used is 0.1% to 5% of the total mass of the three monomers. When the mass percentage of the emulsifier is within this range, the first, second, and third monomers can be emulsified and dispersed in the solvent to form a relatively uniform system.
[0174] In some embodiments, the initiator includes potassium persulfate and / or ammonium persulfate.
[0175] In some embodiments, the ratio of the mass percentage of the initiator to the mass percentage of the second monomer, the second monomer, and the third monomer, based on the total mass of the mixed system, is 0.15% to 1%. That is, the amount of the initiator used is 0.1% to 5% of the total mass of the three monomers. When the mass percentage of the initiator is within this range, sufficient polymerization can be ensured.
[0176] In some embodiments, the solvent may include water, such as deionized water.
[0177] As a specific embodiment, the method includes:
[0178] Preparation of prepolymer: deionized water, emulsifier, first polymerizable monomer, second polymerizable monomer and third polymerizable monomer are mixed and stirred uniformly to obtain a prepolymer;
[0179] Preparation of the first polymer: Add an emulsifier and deionized water to a container, stir and emulsify for 30 to 60 minutes to obtain a uniform and stable emulsion; then slowly dropwise add the prepolymer prepared in the previous step and the initiator solution (the initiator potassium persulfate and / or ammonium persulfate is dissolved in deionized water to form a solution), after the dropwise addition is completed, heat to 90° C. to 110° C. and keep warm for 0.5 hours, cool to 40° C., adjust the pH to 7 to 8 with ammonia water, filter, discharge, and dry to obtain the first polymer.
[0180] In some embodiments, the organosilicon particles further include a second polymer comprising a structural unit represented by formula (a):
[0181]
[0182] In formula (a), R 14 and R 15 Each independently comprises one or more of a substituted or unsubstituted C1-C10 alkyl group, a hydroxyl group or an amino group. 14 and R 15 Each independently includes one or more of a substituted or unsubstituted C1-C6 alkyl group, a hydroxyl group or an amino group.
[0183] Illustratively, the second polymer includes at least one of the structures represented by formula (a-1) to the structures represented by formula (a-5):
[0184]
[0185] Illustratively, the second polymer may include one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane, and polymethylaminosiloxane.
[0186] The first polymer and the second polymer in this application are only used to distinguish the types of materials and have no limiting effect on the order and quantity.
[0187] In some embodiments, the number average molecular weight of the organosilicon particles is 22,000 to 79,000, optionally 24,000 to 48,000. For example, the number average molecular weight of the polymer can be 22,000, 23,000, 24,000, 25,000, 30,000, 35,000, 40,000, 45,000, 46,000, 47,000, 48,000, or a range consisting of any two of the foregoing values. When the number average molecular weight of the organosilicon particles is within the above range, they have a relatively high viscosity, which helps improve the adhesion between the separator and the positive and negative electrode sheets when the organosilicon particles are used in the separator. When the number average molecular weight of the silicone particles is within the above range, it is conducive to the formation of silicone particles with smaller particle size. When applied to the isolation membrane, it can achieve light and thin coating of the coating in the isolation membrane, reduce the overall thickness of the isolation membrane, and thus facilitate the improvement of the energy density of the secondary battery; and the particle size of the silicone particles formed by the polymer will not be too small, which can reduce the risk of silicone particles clogging the substrate in the isolation membrane and improve the overall air permeability and other properties of the isolation membrane.
[0188] In this application, the number average molecular weight of the polymer can be measured by gel permeation chromatography (GPC). Specifically, the measurement is performed using a GPC1515 instrument from Waters, USA. The sample is dissolved in tetrahydrofuran for more than 12 hours at a concentration of 4 mg / ml. The sample is filtered and prepared. The test temperature is 25°C and the test flow rate is 1 ml / min.
[0189] The inventors further discovered that during the long-term charge and discharge process of the secondary battery, the moisture in the isolation membrane will gradually be released and enter the electrolyte. The electrolyte is highly sensitive to moisture and easily produces hydrofluoric acid HF when it comes into contact with water, thereby increasing the acidity of the electrolyte, causing corrosion of active materials and current collectors, etc., and may cause the dissolution of transition metal ions in the active materials, thereby affecting the electrochemical performance of the secondary battery. Therefore, the present application regulates the moisture content of the organosilicon particles to be less than or equal to 3500μg / g; it can be optionally 500μg / g to 3000μg / g, based on the mass of the organosilicon particles. When the moisture content of the organosilicon particles is within the above range, the moisture content contained therein is relatively small, which can reduce the risk of side reactions in the electrolyte during the long-term charge and discharge cycle of the secondary battery, thereby improving the electrochemical performance of the secondary battery. Illustratively, the moisture content of the silicone particles can be 300 μg / g, 500 μg / g, 800 μg / g, 1000 μg / g, 1200 μg / g, 1500 μg / g, 1800 μg / g, 2000 μg / g, 2500 μg / g, 2800 μg / g, 3000 μg / g, 3500 μg / g, or a range consisting of any two of the above values.
[0190] The moisture content of the silicone particles can be measured by a moisture meter. The test method can adopt the Karl Fischer moisture determination method, and the test instrument can adopt the Swiss Metrohm 831 Karl Fischer moisture meter.
[0191] In some embodiments, the mass percentage of the silicone particles is m1%, where 50 ≤ m1 < 100, and optionally, 80 ≤ m1 ≤ 95; this ensures the heat resistance and stability of the coating. For example, the mass percentage of the silicone particles can be 50%, 60%, 70%, 80%, 85%, 90%, 95%, 97%, or a range consisting of any two of these values.
[0192] In some embodiments, the coating layer may further include inorganic particles. By adding inorganic particles, the heat resistance of the coating layer may be further improved.
[0193] In some embodiments, the mass percentage of the inorganic particles in the coating is m2%, where 0<m2≤30. For example, the mass percentage of the inorganic particles in the coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range consisting of any two of the above values.
[0194] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0195] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0196] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z, 0<x<3, 0<y<3, 0<z<7).
[0197] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with olivine structures, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0198] In some embodiments, the coating may also include other organic particles, for example, the organic particles may include at least one of polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate, and mixtures thereof.
[0199] In some embodiments, the coating may further include a binder. For example, the binder may include at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate monomers, or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0200] In some embodiments, the thickness of the coating may be 0.1 μm to 4 μm, optionally 0.5 μm to 3 μm. This helps to improve the energy density of the secondary battery. In this application, the thickness of the coating refers to the thickness of the coating on one side of the substrate. For example, the thickness of the coating can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0201] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 3 μm to 12 μm. The coating of the present application can significantly improve the heat resistance of the separator, thereby allowing the use of a thinner substrate, thereby helping to increase the energy density of the secondary battery. For example, the thickness of the substrate can be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.
[0202] In some embodiments, the porosity of the substrate is greater than or equal to 25%, and can optionally be between 28% and 41%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be guaranteed to be conducive to the migration of active ions. Moreover, due to the relatively small porosity, the mechanical properties of the substrate can be guaranteed, providing good support for the coating.
[0203] The present application does not particularly limit the material of the substrate. Any known substrate with good chemical and mechanical stability can be selected. For example, the substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0204] In some embodiments, the separator may further include an adhesive layer disposed on at least a portion of the coating, the adhesive layer comprising a binder. The adhesive layer not only prevents the coating from falling off, improving the adhesion between the coating and the substrate and the safety of the secondary battery, but also improves the interface between the separator and the electrode, thereby enhancing the cycling performance of the secondary battery.
[0205] Optionally, the binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer. The comonomer includes, but is not limited to, at least one of the following: an acrylate monomer, an acrylic acid monomer, an olefin monomer, a halogen-containing olefin monomer, a fluoroether monomer, and the like.
[0206] Alternatively, the binder includes a vinylidene fluoride based polymer, such as a homopolymer of vinylidene fluoride monomer (VDF) and / or a copolymer of vinylidene fluoride monomer and a comonomer. The comonomer may be at least one of an olefin monomer, a fluorine-containing olefin monomer, a chlorine-containing olefin monomer, an acrylate monomer, an acrylic monomer, and a fluoroether monomer. Alternatively, the comonomer may include at least one of trifluoroethylene (VF3), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro (alkyl vinyl) ether (such as perfluoro (methyl vinyl) ether PMVE, perfluoro (ethyl vinyl) ether PEVE, perfluoro (propyl vinyl) ether PPVE), perfluoro (1,3-dioxole) and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).
[0207] In some embodiments, the longitudinal thermal shrinkage rate η1 of the separator at 150° C. for 1 hour is ≤3.0%.
[0208] In some embodiments, the transverse thermal shrinkage rate η2 of the separator at 150° C. for 1 hour is ≤2.0%.
[0209] The separator of the present application has low thermal shrinkage in both the transverse and longitudinal directions at a high temperature of 150° C., thereby improving the safety performance of the secondary battery.
[0210] In some embodiments, the longitudinal tensile strength R of the separator is m1 ≥2700kg / cm 2 , optionally 2700kg / cm 2 ≤R m1 ≤4500kg / cm 2 .
[0211] In some embodiments, the transverse tensile strength R m2 ≥2000kg / cm 2 , optionally 2500kg / cm 2 ≤R m2 ≤4500kg / cm 2 .
[0212] The separator of the present application has high tensile strength in both the transverse and longitudinal directions. Therefore, when the secondary battery expands, the separator is less likely to be damaged, thereby improving the safety performance of the secondary battery.
[0213] In some embodiments, the wetted length L of the isolation membrane is ≥ 30 mm, optionally 30 mm ≤ L ≤ 60 mm.
[0214] In some embodiments, the wetting speed of the isolation membrane is u≧2 mm / s, optionally 2 mm / s≦u≦4 mm / s.
[0215] The separator of the present application has good wettability and retention properties for the electrolyte, thereby improving the ion conductivity of the separator and the capacity performance of the secondary battery.
[0216] In some embodiments, the separator has an air permeability MAP ≤ 300 secs / 100 mL, optionally 130 secs / 100 mL ≤ MAP ≤ 250 secs / 100 mL. The separator of the present application has good air permeability, thereby improving ion conductivity and secondary battery capacity performance.
[0217] In this application, the thermal shrinkage, tensile strength, and air permeability of the separator have meanings commonly known in the art and can be measured using methods known in the art. For example, they can all be tested in accordance with standard GB / T 36363-2018.
[0218] In this application, the wetting length and wetting speed of the isolation membrane have the meanings well known in the art and can be measured using methods known in the art. An exemplary test method is as follows: cut the isolation membrane into samples with a width of 5 mm and a length of 100 mm, fix the two ends of the sample and place it horizontally; take 0.5 mg of electrolyte and drop it in the center of the sample. After reaching the specified time (1 min in this application), take a picture and measure the length of the electrolyte diffusion, thereby obtaining the wetting length and wetting speed of the isolation membrane. In order to ensure the accuracy of the test results, multiple (for example, 5 to 10) samples can be taken for testing, and the test results are obtained by calculating the average value. The electrolyte can be prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0219] It should be noted that the above-mentioned isolation film coating parameters (such as thickness, etc.) are the coating parameters of a single side of the substrate. When the coating is provided on both sides of the substrate, the coating parameters on either side that meet the requirements of this application are considered to fall within the scope of protection of this application.
[0220] Preparation method
[0221] In a second aspect, the present application provides a method for preparing an isolation membrane, which can be used to prepare the isolation membrane described in any embodiment of the first aspect of the present application.
[0222] The method includes the following steps: S1, providing a substrate; S2, preparing a coating slurry, mixing silicone particles in a solvent to prepare a coating slurry; S3, applying the coating slurry on at least one surface of the substrate to form a coating and drying it to obtain an isolation film, wherein the volume distribution particle size Dv90 of the silicone particles satisfies: 0<Dv90≤3.0μm.
[0223] In some embodiments, 0.1 μm ≤ Dv90 ≤ 2.0 μm.
[0224] In some embodiments, in S2, the solvent may be water, such as deionized water.
[0225] In some embodiments, in S2 , the coating slurry may further include other components, for example, a dispersant, a wetting agent, a binder, etc.
[0226] In some embodiments, in S2, the mass percentage of the silicone particles is ≥50% based on the mass of the coating, and may be 80%-95%. When the mass percentage of the silicone particles is within the above range, the heat resistance and stability of the coating can be significantly improved.
[0227] In some embodiments, the solid content of the coating slurry is 10% to 40%; optionally 20% to 30%.
[0228]
[0229] In some embodiments, in S3, the coating is performed using a coating machine. The present application does not particularly limit the type of coating machine; for example, a commercially available coating machine may be used. The coating machine includes a gravure roller for transferring the slurry to the substrate.
[0230] In some embodiments, in S3, the coating method may be transfer coating, spin spray coating, dip coating, etc.
[0231] In some embodiments, the method further comprises the following steps: S4, secondary coating, coating a slurry containing a binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.
[0232] The method for preparing the isolation membrane of the present application obtains the coating layer through one-time coating, which greatly simplifies the production process of the isolation membrane.
[0233] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane of the present application can refer to the isolation membrane of the first aspect of the embodiment of the present application, and will not be repeated here.
[0234] Unless otherwise specified, all raw materials used in the method for preparing the separator of the present application can be obtained commercially.
[0235] secondary batteries
[0236] In a third aspect, the present application also provides a secondary battery.
[0237] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after discharge to reactivate their active materials for continued use. Typically, a secondary battery comprises an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is positioned between the positive and negative electrodes to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.
[0238] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium-ion battery, a sodium-ion battery, etc. In particular, the secondary battery may be a lithium-ion secondary battery.
[0239] The secondary battery described in the present application includes a separator according to the first aspect of the present application or a separator prepared by the method according to the second aspect of the embodiment of the present application, wherein the separator is spaced between the positive electrode sheet and the negative electrode sheet. Optionally, at least one side of the separator close to the negative electrode sheet has a coating according to the present application. Furthermore, the side of the separator close to the positive electrode sheet has a coating according to the present application, and the side of the separator close to the negative electrode sheet also has a coating according to the present application. As a result, the secondary battery of the present application can improve its own energy density and safety performance, etc.
[0240] [Positive electrode]
[0241] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector has two surfaces that oppose each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.
[0242] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0243] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of a lithium transition metal oxide and a modified compound thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A includes at least one of N, F, S, and Cl.
[0244] As an example, the positive active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0245] When the secondary battery of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0246] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x At least one of the materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes H + 、Li + 、Na + , K + and NH4 +At least one of , M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.
[0247] In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification on the positive electrode active materials.
[0248] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. By way of example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is ≤5% based on the total mass of the positive electrode film layer.
[0249] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.
[0250] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0251] The positive electrode film layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0252] [Negative electrode]
[0253] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0254] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0255] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. By way of example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode film layer.
[0256] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5% based on the total mass of the negative electrode film layer.
[0257] In some embodiments, the negative electrode film layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode film layer.
[0258] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0259] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until uniformly mixed. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0260] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in certain embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) disposed on the surface of the negative electrode current collector and sandwiched between the negative electrode current collector and the negative electrode film layer. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode film layer.
[0261] [Electrolyte]
[0262] During the charge and discharge process of a secondary battery, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected according to actual needs.
[0263] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0264] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0265] When the secondary battery of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0266] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0267] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0268] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0269] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0270] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0271] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG1 shows a secondary battery 5 with a square structure as an example.
[0272] In some embodiments, as shown in FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0273] The method for preparing the secondary battery of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. The secondary battery is obtained through vacuum packaging, static standing, formation, and shaping processes.
[0274] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0275] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.
[0276] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0277] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0278] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0279] Electrical devices
[0280] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0281] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0282] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0283] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0284] Example
[0285] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.
[0286] Preparation of silicone particles
[0287] Example A
[0288] Prepolymer preparation
[0289] 1400 g of deionized water and 7 g of sodium lauryl sulfate were added to a 5L three-necked flask, and the mixture was stirred and emulsified at a speed of 1500 r / min for 30 min to obtain a uniform and stable emulsion. Then, n-butyl acrylate, acrylonitrile and methacryloyloxypropyl cage-type polysilsesquioxane (the molar content ratio of n-butyl acrylate, acrylonitrile and methacryloyloxypropyl cage-type polysilsesquioxane was 15:3:2) were added in sequence, and stirring was continued at a speed of 1500 r / min for 30 min to obtain a uniform prepolymer.
[0290] Preparation of silicone particles
[0291] In a dry three-necked flask, add 3g of emulsifier and 1000g of deionized water, stir and emulsify at high speed for 30min to obtain a uniform and stable emulsion; then use a peristaltic pump to slowly drop the prepolymer and initiator solution prepared in the previous step (dissolve 3g of potassium persulfate as initiator in 30g of deionized water to form a solution), after the addition is completed, heat to 90°C and keep warm for 0.5h, cool to 40°C, adjust the pH to 7-8 with ammonia water, filter, discharge, and obtain silicone particles through a drying process.
[0292] Example 1
[0293] Preparation of isolation membrane
[0294] Provide PE substrate: thickness 7μm, porosity 40%, ion conductivity 1.20mS / cm, average particle size 0.3μm.
[0295] Preparation of coating slurry: The organosilicon particles prepared in Example A, the binder aqueous solution type polyacrylic acid and the additive are mixed uniformly in an appropriate amount of solvent deionized water at a mass ratio of 92:7:1 to obtain a coating slurry.
[0296] Coating: The prepared coating slurry is coated on both surfaces of the PE substrate using a coating machine, and then dried and cut to obtain a separator. The surface density of the coating on one side of the PE substrate is 0.9 g / m 2 , thickness is 0.45μm.
[0297] Preparation of positive electrode
[0298] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0299] The positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (NCM333), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes. The surface density of the positive electrode sheet is 0.207mg / mm 2 , compacted density is 3.5g / cm 3 .
[0300] Preparation of negative electrode sheet
[0301] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0302] Natural graphite, the negative electrode active material, is mixed with Super P (a conductive agent), CMC (a thickener), and SBR (a binder) in deionized water to create a negative electrode slurry. The solids content is 30% by weight, and the mass ratio of graphite, Super P, CMC, and SBR (a binder) is 80:15:3:2. The negative electrode slurry is coated onto a current collector copper foil and dried at 85°C. The negative electrode sheet is then cold-pressed, trimmed, cut, and slit, and then dried at 120°C under vacuum for 12 hours.
[0303] Preparation of electrolyte
[0304] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0305] Preparation of secondary batteries
[0306] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0307] Comparative Example 1, Example 2 to Example 12
[0308] The secondary battery was prepared using a method similar to that of Example 1, except that the preparation parameters of the isolation membrane were different. Specific parameters are shown in Table 1.
[0309] The test results are shown in Table 1.
[0310] Test section
[0311] 1. Thermal shrinkage test of isolation film
[0312] Sample preparation: Punch the prepared isolation film into samples with a width of 50 mm and a length of 100 mm along the TD and MD directions using a punching machine. Place 5 parallel samples on A4 paper, and then place the A4 paper with the samples on corrugated paper with a thickness of 1 mm to 5 mm.
[0313] Sample test: Set the temperature of the blast oven to 150°C. After the temperature reaches the set temperature and stabilizes for 30 minutes, place the A4 paper placed on the corrugated paper into the blast oven, start timing, and after the set time (1 hour in this application) is reached, measure the length and width of the isolation film, and mark the values as a and b respectively.
[0314] Calculation of thermal shrinkage: longitudinal (MD) thermal shrinkage = [(100-a) / 100] × 100%, transverse (TD) thermal shrinkage = [(50-b) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0315] 2. Hot box test of secondary batteries
[0316] At 25°C, the secondary batteries were charged at a constant current of 1C to 4.2V. They were then charged at a constant voltage until the current reached ≤0.05C and allowed to rest for 5 minutes. Each secondary battery was then tested in a DHG-9070A DHG series high-temperature oven with a fixture. The temperature was raised from room temperature to 80±2°C at a rate of 5°C / min and held for 30 minutes. The temperature was then increased again at a rate of 5°C / min, with each 5°C increase lasting 30 minutes, until the secondary battery failed. The surface temperature of the secondary battery was monitored during the heating process. The oven temperature corresponding to the point at which the temperature began to rise sharply was the secondary battery's hot box failure temperature. A higher hot box failure temperature indicates better thermal safety.
[0317] Table 1
[0318]
[0319] Table 1 shows that the Dv90 of the silicone particles in Comparative Example 1 is 3.50 μm. The separator using silicone particles of this particle size has a high thermal shrinkage rate, resulting in poor stability during long-term cycling of lithium-ion batteries. The Dv90 of silicone particles is closely related to the minimum coating thickness of the separator. The maximum thickness is generally less than the Dv90, otherwise coating gaps are likely. For a given coating thickness, a lower Dv90 results in a greater number of accumulated particles and layers, resulting in better heat resistance.
[0320] In Examples 1 to 12, by regulating the Dv90 of the silicone particles to satisfy: 0<Dv90≤3.0μm; especially when satisfying 0.1μm≤Dv90≤2.0μm, the isolation membrane can have a relatively thin coating, which can reduce the thermal shrinkage of the isolation membrane and improve the mechanical properties of the isolation membrane; and the isolation membrane has good air permeability, which is conducive to the migration of active ions. Furthermore, the embodiment can further improve the mechanical properties and air permeability of the isolation membrane by regulating (Dv90-Dv10) / Dv50. Moreover, as the coating thickness increases, more silicone particles are accumulated, and the heat resistance of the isolation membrane is improved, but the air permeability may decrease to a certain extent.
[0321] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A separator comprising a substrate and a coating disposed on at least one surface of the substrate, wherein the coating comprises organic silicon particles, and the volume distribution particle size Dv90 of the organic silicon particles satisfies: 0<Dv90≤3.0μm.
2. The isolation film according to claim 1, wherein 0.1μm≤Dv90≤2.0μm.
3. The separator according to claim 1 or 2, wherein: The particle size distribution of the silicone particles satisfies: (Dv90-Dv10) / Dv50≤2.0; Optionally, 0.1≤(Dv90-Dv10) / Dv50≤1.
0.
4. The separator according to any one of claims 1 to 3, wherein The volume distribution particle size Dv50 of the silicone particles satisfies the following conditions: 0.01 μm≤Dv50≤2 μm.
5. The separator according to any one of claims 1 to 4, wherein The isolation film further satisfies at least one of conditions (1) to (3): (1) The specific surface area (SSA) of the silicone particles is 2.0 cm 2 / g to 50cm 2 / g, optional 8.5cm 2 / g to 20.5cm 2 / g; (2) The organosilicon particles include primary particles; (3) The morphology of the organosilicon particles includes at least one of spherical, quasi-spherical, cubic, rhombic, fibrous, tubular, rod-like and flake-like.
6. The separator according to any one of claims 1 to 5, wherein The organosilicon particles include a first polymer; The first polymer includes a first structural unit, a second structural unit and a third structural unit; The first structural unit includes a structural unit represented by formula (I): In formula (I), R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; R2 includes one or more of a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C1-C20 hydroxyalkyl group; alternatively, R2 includes one or more of a C1-C12 alkyl group, a C3-C12 cycloalkyl group, or a C1-C12 hydroxyalkyl group; The second structural unit includes a structural unit represented by formula (II): In formula (II), R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group; alternatively, R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; The third structural unit includes a structural unit represented by formula (III): In formula (III), R4 to R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, one or more structural units as shown in formula (III-1), and R4 to R 11 At least one of them includes a structural unit represented by formula (III-1), In formula (III-1), R 12 Including one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R 12 including one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group; R 13 Including substituted or unsubstituted C1-C10 alkyl; optionally, R 13 This includes substituted or unsubstituted C3-C10 alkyl groups.
7. The polymer according to claim 6, wherein Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is recorded as A%, 75≤A<100; optionally, 75≤A≤80; and / or Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is recorded as B%, 0<B≤15; optionally, 5≤B≤15; and / or Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is recorded as C%, 0<C≤15; optionally, 5≤C≤15.
8. The polymer according to claim 6 or 7, wherein Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is recorded as A%, the molar content of the second structural unit is recorded as B%, and the molar content of the third structural unit is recorded as C%. The first polymer satisfies one or more of conditions (1) to (3): (1) 5≤A / B≤15; (2) 5≤A / C≤15; (3) A:B:C is (12 to 15):(1 to 3):(1 to 3).
9. The separator according to any one of claims 1 to 8, wherein The organosilicon particles include a second polymer, and the second polymer includes a structural unit represented by formula (a): In formula (a), R 14 and R 15 Each independently comprises one or more of substituted or unsubstituted C1-C10 alkyl, hydroxyl or amino; optionally, R 14 and R 15 Each independently comprises one or more of a substituted or unsubstituted C1-C6 alkyl group, a hydroxyl group or an amino group; Optionally, the second polymer includes one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane and polymethylaminosiloxane.
10. The separator according to any one of claims 1 to 9, wherein The number average molecular weight of the organic silicon particles is 22,000 to 79,000, and can be optionally 24,000 to 48,000.
11. The separator according to any one of claims 1 to 10, wherein Based on the mass of the organosilicon particles, the moisture content of the organosilicon particles is less than or equal to 3500 μg / g; optionally, it can be 500 μg / g to 3000 μg / g.
12. The separator according to any one of claims 1 to 11, wherein Based on the mass of the coating, the mass percentage of the organic silicon particles is m1%, 50≤m1<100, optionally, 80≤m1≤95.
13. The separator according to any one of claims 1 to 12, wherein The coating layer further comprises inorganic particles; optionally, the mass percentage of the inorganic particles in the coating layer is m2%, 0<m2≤30.
14. The separator according to any one of claims 1 to 13, wherein The isolation film further satisfies at least one of conditions (a) to (c): (a) The porosity of the substrate is greater than or equal to 25%; optionally, it is 28% to 41%; (b) the thickness of the substrate is less than or equal to 16 μm; optionally, it is 3 μm to 12 μm; (c) The thickness of the coating is 0.1 μm to 4 μm; optionally 0.5 μm to 3 μm.
15. The separator according to any one of claims 1 to 14, wherein The isolation film further comprises at least one of the following conditions (I) to (VII): (I) the longitudinal heat shrinkage rate η1 of the isolation film at 150°C for 1 hour is ≤3.0%; (II) the transverse heat shrinkage of the isolation film at 150° C. for 1 hour is η2≤2.0%; (III) Longitudinal tensile strength R of the separator m1 ≥2700kgf / cm 2 , optionally, 2700kg / cm 2 ≤R m1 ≤4500kg / cm 2 ; (IV) Transverse tensile strength R of the separator m2 ≥2000kgf / cm 2 , optionally, 2500kg / cm 2 ≤R m2 ≤4500kg / cm 2 ; (V) The wetted length L of the isolation membrane is ≥ 30 mm, optionally, 30 mm ≤ L ≤ 60 mm; (VI) the wetting speed of the isolation membrane u≥2 mm / s, optionally, 2 mm / s≤u≤4 mm / s; (VII) The air permeability of the isolation membrane is MAP≤300 secs / 100 mL, optionally, 130 secs / 100 mL≤MAP≤250 secs / 100 mL.
16. A method for preparing an isolation membrane, comprising: S1, providing substrate; S2, mixing the organosilicon particles in a solvent to form a coating slurry; S3, coating the coating slurry on at least one surface of the substrate to form a coating and drying to obtain a separator, The volume distribution particle size Dv90 of the organic silicon particles satisfies: 0<Dv90≤3.0 μm.
17. The preparation method according to claim 16, wherein Based on the mass of the coating, the mass percentage of the silicone particles is greater than or equal to 50%; optionally 80% to 95%; and / or The solid content of the coating slurry is 10% to 40%, and optionally 20% to 30%. 18 . A secondary battery comprising the separator according to claim 1 or the separator prepared by the preparation method according to claim 16 or 17.
19. An electric device comprising the secondary battery according to claim 18.
Citation Information
Patent Citations
Spherical silicon resin micro-powder coating diaphragm and preparation method and application thereof in lithium ion battery
CN112038548A
Separator for nonaqueous secondary battery, and nonaqueous secondary battery
JP2010176936A
Polyolefin microporous membrane and separator for lithium ion battery
JP2011006585A
Organic silicone fine particle, method of producing organic silicone fine particle, modified polyolefin microporous film, method of producing modified polyolefin microporous film and separator for nonaqueous electrolyte electric cell
JP2014173016A
Separator with improved thermal safety for electrochemical device and method of making the same
KR1020160097958A
Cited By
Electrochemical device and electronic device
CN119833555A
